Detection of CA19-9 using fluorescent polymer imprinted membranes - Xu, Ana (2024)
(Introduction) The Carbohydrate antigen19-9 (CA19-9) is a biomarker widely used for the diagnosis and monitoring of various types of cancer, especially pancreatic cancer (PC). Molecularly Imprinted Polymers (MIPs) are synthetic materials with recognition sites molecularly designed to bind selectively to a target analyte, providing high specificity and sensitivity. In this work, the use of solid supports such as membranes, was used to imprint the MIPs, allowing the creation of robust and easy-to-manipulate biomimetic sensors for the precise and efficient detection of biomarkers, specifically CA19-9.